Impact of initial models and variable accretion rates on the pre-main-sequence evolution of massive and intermediate-mass stars and the early evolution of H II regions - Haemmerlé, Lionel; Peters, Thomas (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. Massive star formation requires the accretion of gas at high rate while the star is already bright. Its actual luminosity depends sensitively on the
Gesehen am 04.09.2020